Recovery of preoperative absolute knee extension and flexion strength after ACL reconstruction - Ramana Piussi; Daniel Broman; Erik Musslinder; Susanne Beischer; Roland Thomeé; Eric Hamrin Senorski (BMC, 2020)
Abstract Background The recovery of muscle function after an Anterior Cruciate Ligament (ACL) reconstruction is most commonly reported as limb-to-limb differences using the Limb Symmetry Index (LSI), which is not free from limitations. The purpose of this study was to compare the proportion of patients who recover their Preoperative Absolute Muscle Strength (PAMS) 8 and 12 months after ACL reconstruction with the proportion of patients who recover their symmetrical knee strength. A secondary aim was to assess the relationship between psychological Patient-Reported Outcomes (PROs) and recovering PAMS at 8 and 12 months after ACL reconstruction and rehabilitation. Method Preoperative, 8- and 12-month results from quadriceps and hamstring strength tests and PROs for 117 patients were extracted from a rehabilitation registry. Individual preoperative peak torques from strength tests were compared with results from the 8- and 12-month follow-ups respectively. Patients were defined as having recovered their PAMS upon reaching 90% of their preoperative peak torque for both quadriceps and hamstring strength. Patients were defined as having recovered their LSI upon reaching a value ≥90% when comparing the results for their injured knee with those of their healthy knee. Correlations between the recovery of PAMS and PROs at 8 and 12 months were analyzed. Results There was no difference in the proportion of patients who recovered their PAMS compared with patients who recovered their LSI. In all, 30% and 32% of the patients who recovered their LSI had not recovered their PAMS at 8 months and 12 months respectively. In the patients who had recovered their PAMS, 24% and 31% had not recovered their symmetrical LSI at 8 months and 12 months respectively. There was no significant correlation between the recovery of PAMS and psychological PROs. Conclusion The use of both PAMS and LSI provides more detailed information on the recovery of muscle strength after ACL reconstruction. The recovery of PAMS was not correlated with psychological traits, which implies that both PROs and PAMS are important when evaluating patients after ACL reconstruction. Trial registration  This trial was not registered.